2011
DOI: 10.1097/mca.0b013e3283441d28
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking on acute phase outcomes of myocardial infarction

Abstract: A beneficial effect of smoking ('smoker's paradox') in the unadjusted primary end point continues to be present; however, after adjustment for differences in baseline characteristics, no benefit was detectable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 0 publications
0
9
1
1
Order By: Relevance
“…However, it is also well known that smokers are at greater risk for development of cancer and other pulmonary disease during followup. Although this issue might be relevant to the low early cardiac mortality and late noncardiac mortality in our study, our data do not allow an assessment of the proportion of habitual smokers, and recent studies do not support the existence of a "smoker's paradox" (24,25).…”
Section: Discussioncontrasting
confidence: 61%
“…However, it is also well known that smokers are at greater risk for development of cancer and other pulmonary disease during followup. Although this issue might be relevant to the low early cardiac mortality and late noncardiac mortality in our study, our data do not allow an assessment of the proportion of habitual smokers, and recent studies do not support the existence of a "smoker's paradox" (24,25).…”
Section: Discussioncontrasting
confidence: 61%
“…When these baseline differences were corrected for by multivariate analysis, smoking status was no longer an independent predictor of survival. Similarly, in a recent study including 1424 STEMI patients undergoing rescue or primary angioplasty, Wakabayashi et al [25], found a beneficial effect of smoking on clinical outcome, that disappeared after adjustment for differences in baseline characteristics. However, Katayama et al [26], among 367 STEMI patients undergoing primary angioplasty, found that smoking was associated with lower mortality rates, potentially explained by less damage to the microvascular function (as evaluated by ST-segment resolution) and better ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Wakabayashi K. с соавт. [31] про-анализировали данные 1424 больных с ИМ, которым были выполнены чрезкожные коронарные вмеша-тельства с установкой стентов с лекарственным по-крытием, и которых они разделили на 3 группы, в том числе -курящих на момент развития ИМ (n=486), бросивших курить (n=349) и никогда не куривших (n=589). Авторы также выявили, что курящие паци-енты были достоверно моложе по сравнению с нико-гда не курившими (p<0,001).…”
Section: Smoking As a Risk Factor Of Cardiovascular Diseases курение unclassified